Neither Naïve nor Evil: Framing and Dominant Strategies in Decision-making in Contexts of Ignorance - González de Requena Farré, Juan Antonio (Pensando Psicología, 2015)
Introduction: Numerous psychological research studies about decision-making address both risk and ignorance under the category of decision in contexts of uncertainty.Objective: In this research work, the aim is to specifically describe the ways certain decision rules are used in a context of ignorance in the context of different consequences, affected parties and properties. In this way, it is possible to determine whether or not some of the ways of framing a decision that have been observed in contexts of risk actually occur, such as those considered by the prospective theory of Kahneman and Tversky.Methodology: A comparative study of the results was made of the results of a questionnaire with 24 gambling situations with different properties, affected parties and consequences, which was then applied to a sample of 232 people with their informed consent.Results: The results showed significant differences in the use of decision criteria in contexts of ignorance, with a clear predominance of the conservative strategy.Conclusions: It may be concluded that in contexts of decision-making in ignorance, aversion to loss becomes acute and the framing effect observed in low-risk decisions is slightly modified, because more risk is not necessarily run in a perspective of loss.
Keywords: contexts of ignorance; rational choice; framing; decision rules